How Can Burundi Raise its Growth Rate? : The Impact of Civil Conflicts and State Interventionon Burundi's Growth Performance - Basdevant, Olivier (IMF Working Papers; Working Paper ;, 2009)
Over the last thirty years Burundi's low economic growth has led to a significant decline in per capita GDP. The purpose of this paper is to shed light on supply-side constraints that prevented Burundi's economy from growing faster. Lack of investment, civil conflict, economic inefficiencies, state intervention in the economy, and regulatory restrictions explain a large part of the weak growth performance for the last thirty years.